2002
DOI: 10.1123/apaq.19.3.261
|View full text |Cite
|
Sign up to set email alerts
|

The Consultation Process: Adapted Physical Education Specialists’ Perceptions

Abstract: The purpose was to examine adapted physical education (APE) specialists' perceptions about consultation as a delivery model for individuals with disabilities. Six APE specialists (4 female, 2 male) from California participated in this phenomenological study. Data came from in-depth individual interviews, field observations, researcher notes, and focus group interactions. Analysis revealed distinct categories related to consultation: definition, contextual factors, effectiveness (benefits, barriers, documentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…With increased training in IPE, this support could be maximised in assisting the students and the teacher (Davis et al, 2007). APE specialists are a fundamental support and resource for including students with disabilities in GPE (Lytle & Hutchinson, 2004;Lytle & Collier, 2002;Kudláček et al, 2008). Developing study programs at universities and teacher training institutions specialising in Adapted Physical Education/Activity would be greatly beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased training in IPE, this support could be maximised in assisting the students and the teacher (Davis et al, 2007). APE specialists are a fundamental support and resource for including students with disabilities in GPE (Lytle & Hutchinson, 2004;Lytle & Collier, 2002;Kudláček et al, 2008). Developing study programs at universities and teacher training institutions specialising in Adapted Physical Education/Activity would be greatly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…They have undergone specialised training and have a true understanding of the inclusion process. A study by Lytle and Collier (2002) investigated APE specialists' perceptions of consultation. Six participants were involved in the study, four female and two male, with age ranging from thirty five to forty six years and case loads of students ranging from twenty four to one hundred and ten.…”
Section: Support Personnel In Inclusive Physical Educationmentioning
confidence: 99%
“…As the child progresses, motor instruction expands based on the child's ability to grasp more complex skills (Logsdon et al 1997). Collaboration between team members provides the continuity and consistency in instruction within an inclusive environment (Lytle and Collier 2002;Neal et al 2004). It is highly recommended that outside of the group setting or when advancing to the next grade, team members use the same concepts, consistent vocabulary, teaching strategies such as visual supports or prompts, and feedback to the child.…”
Section: Collaboration and Teaching Strategiesmentioning
confidence: 98%
“…Kelly and Gansender (1998) have pointed out that APE can provide both direct and indirect services, while direct services mean direct teaching of children with disabilities and indirect service means providing support to teachers attempting to include children with disabilities in their GPE. A study by Lytle and Collier (2002) investigated APE specialists' perceptions of consultation. Results indicated that the skills, attitudes and knowledge of the APE specialist combined with the educational environment were influential factors in the types of services provided.…”
Section: Adapted Physical Education Teacher/ Consultant Occupation Dementioning
confidence: 99%